Asymptomatic Females Are at Higher Risk for Perioperative TIA/Stroke and Males Are at Higher Risk for Long-Term Mortality after Carotid Artery Stenting: A Vascular Quality Initiative Analysis - Erben, Young; Li, Yupeng; Da Rocha-Franco, Joao A.; Tawk, Rabih G.; Barrett, Kevin M.; Freeman, William D.; Lin, Michelle; Huang, Josephine F.; Miller, David; Farres, Houssam; Brott, Thomas G.; Meschia, James F.; Hakaim, Albert G. (International Journal of Angiology, 2020)
The study aims to review the sex differences with respect to transient ischemic attack (TIA)/stroke and death in the perioperative period and on long-term follow-up among asymptomatic patients treated with carotid stenting (CAS) in the vascular quality initiative (VQI). All cases reported to VQI of asymptomatic CAS (ACAS) patients were reviewed. The primary end point was risk of TIA/stroke and death in the in-hospital perioperative period and in the long-term follow-up. The secondary end point was to evaluate predictors of in-hospital perioperative TIA/stroke and mortality on long-term follow-up after CAS. There were 22,079 CAS procedures captured from January 2005 to April 2019. There were 5,785 (62.7%) patients in the ACAS group. The rate of in-hospital TIA/stroke was higher in female patients (2.7 vs. 1.87%, p = 0.005) and the rate of death was not significant (0.03 vs. 0.07%, p = 0.66). On multivariable logistic regression analysis, prior/current smoking history (odds ratio = 0.58 [95% confidence interval or CI = 0.39–0.87]; p = 0.008) is a predictor of in-hospital TIA/stroke in females. The long-term all-cause mortality is significantly higher in male patients (26.9 vs. 15.7%, p < 0.001). On multivariable Cox-regression analysis, prior/current smoking history (hazard ratio or HR = 1.17 [95% CI = 1.01–1.34]; p = 0.03), coronary artery disease or CAD (HR = 1.15 [95% CI = 1.03–1.28]; p = 0.009), chronic obstructive pulmonary disease or COPD (HR = 1.73 [95% CI = 1.55–1.93]; p < 0.001), threat to life American Society of Anesthesiologists (ASA) class (HR = 2.3 [95% CI = 1.43–3.70]; p = 0.0006), moribund ASA class (HR = 5.66 [95% CI = 2.24–14.29]; p = 0.0003), and low hemoglobin levels (HR = 0.84 [95% CI = 0.82–0.86]; p < 0.001) are the predictors of long-term mortality. In asymptomatic carotid disease patients, women had higher rates of in-hospital perioperative TIA/stroke and a predictor of TIA/stroke is a prior/current history of smoking. Meanwhile, long-term all-cause mortality is higher for male patients compared with their female counterparts. Predictors of long-term mortality are prior/current smoking history, CAD, COPD, higher ASA classification of physical status, and low hemoglobin level. These data should be considered prior to offering CAS to asymptomatic female and male patients and careful risks versus benefits discussion should be offered to each individual patient.
Keywords: carotid endarterectomy; carotid stenosis; carotid stent; internal carotid artery; artery; atherosclerosis